HUBUNGAN PENGETAHUAN KANKER PAYUDARA DENGAN PERILAKU SADARI PADA REMAJA PUTRI DI SMA NEGERI 1 MANADO - Nadia Lady Carolina Malingkas; Sefti Rompas; Kristamuliana (JURNAL KEPERAWATAN, 2023)
Background Breast cancer is one of the most common causes of death for women in Indonesia. One of the reasons for the increased death rate from breast cancer is that it is detected at an advanced stage. SADARI is a technique to detect breast cancer at an earlier stage. Aim The purpose of this research was to determine the relationship between knowledge of breast cancer and SADARI behavior in teenage girls at SMA Negeri 1 Manado. Methods The research method uses the quantitative method, comparative design with a cross sectional approach. The research population is teenage girls in SMA Negeri 1 Manado with a total sample of 143 samples selected using the Simple Random Sampling technique. Data collection was conducted by utilizing a questionnaire and data analysis using Chi Square. Results The results showed that knowledge of breast cancer was good 53.1%, moderate 45.5%, bad 1.4%, and good SADARI behavior 2.1%, moderate 54.5%, bad 43.4%. Conclusions There is no relationship between knowledge of breast cancer and SADARI behavior in teenage girls at SMA Negeri 1 Manado. Suggestions for the nursing care are it is hoped that they can work together with the school to conduct counseling about SADARI. Keywords: Knowledge, Breast Cancer, Behavior, SADARI.